2016
DOI: 10.1002/jmor.20526
|View full text |Cite
|
Sign up to set email alerts
|

The comparative gastrointestinal morphology of Jaculus jaculus (Rodentia) and Paraechinus aethiopicus (Erinaceomorpha)

Abstract: Jaculus jaculus (Lesser Egyptian jerboa) and Paraechinus aethiopicus (Desert hedgehog) are small mammals which thrive in desert conditions and are found, among others, in the Arabian Peninsula. Jaculus jaculus is omnivorous while P. aethiopicus is described as being insectivorous. The study aims to describe the gastrointestinal tract (GIT) morphology of these animals which differ in diet and phylogeny. The GITs of J. jaculus (n = 8) and P. aethiopicus (n = 7) were weighed, photographed, and the length, basal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 23 publications
5
18
0
Order By: Relevance
“…Similar V‐shaped mucosal folds to those observed in T. splendens have been observed in insectivorous rodents Acomys spinosissimus (Southern African spiny mouse) (Boonzaier et al, ) and Jaculus jaculus (Lesser Egyptian jerboa) (Pereira et al, ), but not reported in other African mole‐rat species (Kotzé et al, ). These folds have been postulated to slow down the flow of digesta (Sperber et al, ; Björnhag & Snipes, ) and it is interesting that in T. splendens both a colonic groove and herring‐bone patterned colonic folds were observed.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar V‐shaped mucosal folds to those observed in T. splendens have been observed in insectivorous rodents Acomys spinosissimus (Southern African spiny mouse) (Boonzaier et al, ) and Jaculus jaculus (Lesser Egyptian jerboa) (Pereira et al, ), but not reported in other African mole‐rat species (Kotzé et al, ). These folds have been postulated to slow down the flow of digesta (Sperber et al, ; Björnhag & Snipes, ) and it is interesting that in T. splendens both a colonic groove and herring‐bone patterned colonic folds were observed.…”
Section: Discussionsupporting
confidence: 76%
“…The colonic groove of H. emini resembled that of Georychus capensis (Cape mole-rat) in that the groove walls were low ridges and was wide in the proximal colon and narrowed as it progressed to the distal colon (Kotz e et al, 2009). However, the papillae were not as robust as described in the other Bathyergidae, but was more delicate and similar to that observed in H. glaber Similar V-shaped mucosal folds to those observed in T. splendens have been observed in insectivorous rodents Acomys spinosissimus (Southern African spiny mouse) (Boonzaier et al, 2013) and Jaculus jaculus (Lesser Egyptian jerboa) (Pereira et al, 2016), but not reported in other African mole-rat species (Kotz e et al, 2010). These folds have been postulated to slow down the flow of digesta (Sperber et al, 1983;Bj€ ornhag & Snipes, 1999) and it is interesting that in T. splendens both a colonic groove and herring-bone patterned colonic folds were observed.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The macroscopic lack of differentiation between the small and large intestine, due to the absence of a cecum, in the present species was previously observed also in the Hottentot golden mole ( A. hottentotus ), as well as the other insectivorous small mammals including the Reddish‐gray musk shrew ( C. cyanea ; Boonzaier et al, ), Tailless tenrec ( Tenrec ecaudatus ; Mitchell, ), and Desert hedgehog ( Paraechinus aethiopicus ; Pereira et al, ). The absence of a cecum, taeniae, haustra, or any form of specialization of the combined small and large intestine is seen in various insectivorous mammals (Stevens & Hume, ).…”
Section: Discussionsupporting
confidence: 74%
“…When present, the stomach content was examined macroscopically using a Leica MZ6 dissecting microscope ( Leica Microsystems, Oberkochen, Germany). Furthermore, a representative stomach content sample was prepared for histological examination by processing to wax, sectioning, and staining with H&E. Fiji by ImageJ software (National Institute of Health) was used to measure the areas of recognizable material (plant, insect and/or seed) and expressed as a percentage of the total recognizable material seen on the section (Pereira et al, ).…”
Section: Methodsmentioning
confidence: 99%